2013
DOI: 10.1088/0026-1394/50/1/73
|View full text |Cite
|
Sign up to set email alerts
|

Removal of mercury contamination on primary mass standards by hydrogen plasma and thermal desorption

Abstract: The removal of a high mercury contamination on a Pt reference mass by thermal desorption was studied directly by x-ray photoemission spectroscopy (XPS). Subsequently the contamination mechanism was investigated. Samples of PtIr and AuPt exposed to vapour of mercury in air were studied using XPS and gravimetric mass determination. We find an extremely rapid mercury contamination which takes place within minutes and reaches an initial equilibrium state after 2 h to 4 h. Roughly 1 to 2 monolayers of mercury adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…As very recently reported [29] mechanical polishing can activate the surface and result in an enhanced speed and level of contamination. The different contaminations obtained for an unpolished gold coating and polished samples support this.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…As very recently reported [29] mechanical polishing can activate the surface and result in an enhanced speed and level of contamination. The different contaminations obtained for an unpolished gold coating and polished samples support this.…”
Section: Introductionmentioning
confidence: 65%
“…It is well known in surface physics that polishing alone cannot remove all surface contaminants [22,23]. Furthermore, it was shown that mechanical treatment can increase the surface activity [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Storage conditions (air, vacuum, inert gas) and cleaning methods (alcohol, UV/Ozone, plasma, or thermal desorption) are also factors that affect mass stability. [12][13][14][15][16][17] To understand how surface behaviour affects mass stability after the artefact has been cleaned using different methods and stored under different conditions, it is essential to characterize surface quality by rugosimetric methods (for example, optical scatterometer or X-ray reflectometer, SNOM, or atomic force microscopy 18,19 ) to evaluate mass stability by gravimetric methods by means of mass comparators as well as to identify surface contaminants using spectrometric techniques (for example, XPS (X-Ray photoelectron spectrometry) or ToF-SIMS (Time-of-Flight Secondary ion mass spectrometry)).…”
Section: B Mass Stability and Surface Characterizationmentioning
confidence: 99%
“…In particular, the effect of mercury contamination on the mass of platinum-iridium mass standards has received renewed attention, as has the general topic of improved methods of removing carbonaceous surface contamination from artefacts [26][27][28][29][30][31][32][33].…”
Section: The Bipm Ensemble Of Reference Mass Standardsmentioning
confidence: 99%